RELIABILITY ANALYSIS OF LEAD (LEADER EFFECTIVENESS AND ADAPTABILITY DESCRIPTION) - Baquero Pecino, Clara; Sánchez Santa-Bárbara, Emilio (Anales de Psicología / Annals of Psychology, 2000)
In spite of the recognized attractiveness of the Situational Leadership Theory and of its use as a tool for management training, it is remarkable the shortage of empirical studies to test its assumptions or the psychometric properties of the instruments associated to the model. In the present study, it is analyzed the reliability of the LEAD, instrument designed to evaluate leadership style and effectiveness. A sample of 101 basketball referees was used, to whom the LEAD-Self was administered in two occasions to obtain its reliability through the test-retest method. Also, the reliability was obtained through the internal consistency of the test. Results indicate acceptable levels of reliability of the instrument through the test-retest method, but insufficient internal consistency.